The Effect of FIFA 11+ Training on the Improvement of Speed among Soccer Players at SSB Spartan FC - Riyanto, Dandung Panji; Sumartiningsih, Sri; Hooi, Limboon (Universitas Negeri Semarang, 2024)
Abstract. The aim of this study was to determine the effect of FIFA 11+ training on the speed improvement of SSB Spartan FC football players. The population of this study consisted of 20 players, all of whom were included as the sample through a saturation sampling technique. This study employed a quasi-experimental method with a one-group pretest–posttest design, in which measurements were taken before and after the intervention to assess the effect of FIFA 11+ training on players’ speed. The training program was implemented for 45 minutes per session over a period of four weeks. Speed performance was measured using a 20-meter sprint test. The results showed that the average speed before training (pretest) was 3.80 seconds, while after training (post-test) it improved to 3.60 seconds. The paired t-test results yielded a p-value of 0.000, indicating that p < 0.05 and, therefore, the null hypothesis (H₀) was rejected. It can be concluded that FIFA 11+ training had a significant effect on improving the speed of SSB Spartan FC football players. Abstrak. Tujuan penelitian ini adalah untuk mengetahui pengaruh latihan FIFA 11+ terhadap peningkatan kecepatan pemain sepak bola SSB Spartan FC. Populasi dalam penelitian ini berjumlah 20 pemain, yang seluruhnya dijadikan sampel dengan teknik sampling jenuh. Penelitian ini menggunakan metode eksperimen semu (quasi-experimental) dengan rancangan one group pretest–posttest design, yaitu pengukuran dilakukan sebelum dan sesudah perlakuan untuk mengetahui pengaruh latihan FIFA 11+ terhadap peningkatan kecepatan pemain. Program latihan dilaksanakan selama 4 minggu dengan durasi 45 menit setiap sesi. Pengukuran kecepatan dilakukan menggunakan tes lari sprint 20 meter. Hasil penelitian menunjukkan bahwa rata-rata kecepatan sebelum latihan (pretest) adalah 3,80 detik, sedangkan setelah latihan (posttest) meningkat menjadi 3,60 detik. Hasil uji-t berpasangan (paired t-test) menunjukkan nilai p = 0,000, yang berarti p < 0,05 sehingga H₀ ditolak. Dengan demikian, dapat disimpulkan bahwa latihan FIFA 11+ berpengaruh signifikan terhadap peningkatan kecepatan pemain sepak bola SSB Spartan FC.